2016
DOI: 10.1021/acsami.6b11939
|View full text |Cite
|
Sign up to set email alerts
|

Halochromic Isoquinoline with Mechanochromic Triphenylamine: Smart Fluorescent Material for Rewritable and Self-Erasable Fluorescent Platform

Abstract: Halochromic isoquinoline attached mechanochromic triphenylamine, N-phenyl-N-(4-(quinolin-2-yl)phenyl)benzenamine (PQPBA) and tris(4-(quinolin-2-yl)phenyl)amine (TQPA), smart fluorescent materials exhibit thermo/mechanochromism and tunable solid state fluorescence and their unusual halochromic response in PMMA matrix have been used for fabricating rewritable and self-erasable fluorescent platforms. PQPBA and TQPA showed strong fluorescence in solution (Φ = 0.9290 (PQPBA) and 0.9160 (TQPA)) and moderate solid st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(67 citation statements)
references
References 68 publications
1
66
0
Order By: Relevance
“…The invisibility of the letters on paper under visible light reminds us that the paper coated with polycrystals of 1 can be applied as rewritable PL paper. To date, research on rewritable paper was mainly focused on the mechanochromism, solvatochromism, and photochromism, and so on, while the application of PL materials in rewritable PL paper was seldom reported. Owing to the competition between kinetic and thermodynamic crystallization processes during the cooling process of the molten of 1 , heating the designated area on the paper above T m1 would melt the polycrystals, and IL@2 with red emission would be formed after natural cooling the molten to RT.…”
Section: Figurementioning
confidence: 99%
“…The invisibility of the letters on paper under visible light reminds us that the paper coated with polycrystals of 1 can be applied as rewritable PL paper. To date, research on rewritable paper was mainly focused on the mechanochromism, solvatochromism, and photochromism, and so on, while the application of PL materials in rewritable PL paper was seldom reported. Owing to the competition between kinetic and thermodynamic crystallization processes during the cooling process of the molten of 1 , heating the designated area on the paper above T m1 would melt the polycrystals, and IL@2 with red emission would be formed after natural cooling the molten to RT.…”
Section: Figurementioning
confidence: 99%
“…The incorporation of non-planar carbazole triarylamine unit coupled with solid state fluorescence of 2 and 4 is expected to exhibit stimuli-induced fluorescence switching since such non- 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 planar triphenylamine based derivatives are known to show AEE and mechanofluorochromism (MFC). [46][47][48][49][50][51][52] Crystalline materials of 2 and 4 showed fluorescence l max at 533 and 550 nm, respectively ( Figure 5, F f = 3.06, 2.26). The fluorescence spectra of 2 also showed a small hump at 550 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Thei nvisibility of the letters on paper under visible light reminds us that the paper coated with polycrystals of 1 can be applied as rewritable PL paper.T od ate,r esearch on rewritable paper was mainly focused on the mechanochromism, [16] solvatochromism, [17] and photochromism, [18] and so on, [19] while the application of PL materials in rewritable PL paper was seldom reported. Owing to the competition between kinetic and thermodynamic crystallization processes during the cooling process of the molten of 1,h eating the designated area on the paper above T m1 would melt the polycrystals,a nd IL@2 with red emission would be formed after natural cooling the molten to RT.T he written contents can hardly be photocopied, which provides the opportunity for high-level anti-counterfeiting technology.T .A ida et al firstly reported the Cu I pyrazolate complexes with thermally tunable dichroic emission and their application in thermally rewritable phosphorescent paper as next-generation security technology.…”
Section: Angewandte Chemiementioning
confidence: 99%